The Incipit Code - A Semiotical Approach In (Desferal) The Novel By Nawzat Shamdin (College of Basic Education Research Journal, 2025)
This research aims to establish and explore  concept of code, a concept that Arabs have known since ancient times and  called it cryptography", linked to signs and symbols. However, its modern concept is linked with approaches of linguist Ferdinand De Saussure in early twentieth century, to form  cornerstone of semiotic thinking that represents a semantic interchange relationship between two elements. Research focused on  initiation of  novel (Desferal) by  expatriate Iraqi novelist Nawzat Shamdin. Initiation is described as the condensed core of the text that is related to  overall structure of  work, and because initiation contradicts with its direct communicative language, it concealed many codes that current research attempted to deconstruct and identify their possible semantic dimensions, benefiting in particular - from procedural concepts of codes of event and  symbol, which were established by French critic and philosopher Roland Barthes.
Keywords: Code; Cryptography; Semiotics; Initiation; Symbol; Event